1991
DOI: 10.1071/mf9910423
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and spatial overlap between stream populations of a native and two introduced fish species in New Zealand

Abstract: Benthic and drifting invertebrates as well as fish were sampled in a lake-inlet stream over a 24-h period in summer in order to investigate interactions for food and space between a native fish species (Galaxias brevipinnis, Galaxiidae) and juveniles of two exotic fish species (Salmo trutta and Oncorhynchus mykiss, Salmonidae) in New Zealand. Galaxias brevipinnis fed almost exclusively at night on the benthos, whereas both trout species fed mostly during the day on drifting and benthic prey. Larvae of Deleatid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
3
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 18 publications
3
39
3
1
Order By: Relevance
“…Size selection of prey has also been demonstrated in wild fish (Glova & Sagar 1991, 1993Glova et al 1992), and in the laboratory (Ringler 1979), so prey size may well be the most important factor affecting prey vulnerability to drift-feeding brown trout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Size selection of prey has also been demonstrated in wild fish (Glova & Sagar 1991, 1993Glova et al 1992), and in the laboratory (Ringler 1979), so prey size may well be the most important factor affecting prey vulnerability to drift-feeding brown trout.…”
Section: Discussionmentioning
confidence: 99%
“…The total abundance and biomass of benthic invertebrates were also greater in most willowed than non-willowed sections of these streams, as were the abundance and biomass of several invertebrate taxa. In New Zealand, juvenile brown trout have been shown to feed selectively on particular macroinvertebrate taxa and sizes of prey (Glova & Sagar 1991, 1993Glova et al 1992). Therefore, the objectives of the present study were to determine quantitatively differences in abundance and biomass of potential prey associated with the density of riparian willows, compare the foods consumed by juvenile brown trout in willowed and non-willowed sections of streams, and assess whether juvenile brown trout show consistent preferences for particular macroinvertebrate taxa.…”
Section: Introductionmentioning
confidence: 99%
“…There have been various reports of trout diet overlapping with that of galaxiids in New Zealand, and suggestions that competition for food may partly explain the incompatibility of some galaxiids and trout (Cadwallader 1975;Glova & Sagar 1991;Kusabs & Swales 1991). However, McDowall (2003) suggested that there might be complex interactions between stream dwelling galaxiids and trout, and that the intensity of trout predation on fish and invertebrates may result in galaxiid populations being food limited.…”
Section: Journal Of the Royal Society Of New Zealand Volume 34 2004mentioning
confidence: 99%
“…Representatives of the caddisfly family Hydrobiosidae are widely distributed in rivers throughout New Zealand (Quinn & Hickey 1990) where they can be relatively abundant (e.g., Winterbourn 1978) and comprise important components in the diet of some fish (e.g., Sagar & Eldon 1983;Stephens 1989;Glova & Sagar 1991). The relatively high mobility of the larvae may enable them to adjust to rapidly changing hydraulic conditions in a river, and they might therefore be expected to exhibit strong relationships with hydraulic variables.…”
Section: Introductionmentioning
confidence: 99%